Localization of micro bronchial stump fistulas via guidewire exploration: A case report - Jieqiong Wang; Yan Hang; Zhongliang He; Shunxin Xin; Congbin Peng; Guohong Mo; Weihua Xu (Respirology Case Reports)
Abstract Bronchopleural fistula (BPF), a common complication of lobectomy, is a pathological communication between the bronchus and the pleural space. The bronchial stump fistula (BSF), which is located on the bronchial stump, is a specific type of BPF. BSF can be directly diagnosed via bronchoscopy. However, identification becomes difficult when the BSF is very small (less than 1 mm), referred to as micro BSF in this study because it cannot be found during bronchoscopic exploration. This clinical dilemma easily leads to misdiagnosis of BSF. In this paper, a new procedure for locating micro BSFs using guidewire exploration was reported. This innovative approach involves the use of a guidewire to detect suspected micro BSFs. If the guidewire successfully penetrates the bronchial stump, it indicates the presence of a micro BSF; otherwise, there is none. After precise localization of three micro BSFs, submucosal injection of lauromacrogol around them was performed followed by thoracic fenestration.